Hydroids (Cnidaria, Hydrozoa) from the Vema and Valdivia seamounts (SE Atlantic) - Gil, Marta; Ramil, Fran (European Journal of Taxonomy, 2021)
In this report, we analyse the benthic hydroids collected on the Vema and Valdivia seamounts during a survey conducted in 2015 in the SEAFO Convention Area, focused on mapping and analysing the occurrence and abundance of benthopelagic fish and vulnerable marine ecosystem (VMEs) indicators on selected Southeast Atlantic seamounts. A total of 27 hydroid species were identified, of which 22 belong to Leptothecata and only five to Anthoathecata. Monostaechoides gen. nov. was erected within the family Halopterididae to accommodate Plumularia providentiae Jarvis, 1922, and a new species, Monotheca bergstadi sp. nov., is also described. Campanularia africana is recorded for the first time from the Atlantic Ocean, and the Northeast Atlantic species Amphinema biscayana, Stegopoma giganteum and Clytia gigantea are also recorded from the South Atlantic. Three species were identified to the genus level only, due to the absence of their gonosomes. None of the reported species are endemic, and the hydroid community is clearly dominated by species with a wide geographical distribution in the three major oceans. Only Monotheca bergstadi sp. nov. presently has its distribution restricted to the Vema Seamount and the South African coast.